(untitled) (Journal of Oriental Studies, 2021)
It is known that the literary language of any nation has gone through several stages of development. Similarly, the literary language of the Turkic peoples has passed through several stages and has reached our days. During the reign of the Karakhanids, the medieval Turkic literary language was formed within the framework of Islamic civilization with the introduction of Arabic and Persian words into the Turkic language. The literary language of the Turkic peoples who inhabited Transoxiana, Khorasan and Central Asia existed until the beginning of the twentieth century. There is no consensus in science about the chronology and the name of the last thousand years of the history of the Turkic literary language. The Turkic literary language of the XV-XVII centuries. from the second half of the XIX century it became known as the «Chagatai language», and since the 30s of the XX century it was studied as the "old Uzbek language". Turkologists associate the name of the literary language of that era «Chagatai» with the fact that the poets of that era lived in the Chagatai ulus. However, poets of that time (Lutfi, Atai, Navoi, etc.) wrote that their works were written in the «Turkic language». It is also known that the Turkic literary language was widely used in the khanates formed after the collapse of the Ulus of Jochi. And after the October Revolution, the «old Uzbek language» took the place of the «Chagatai language». There are several reasons for this. The most important were the positions of the pan-Turkic political leaders of the early 20th century, such as Mustafa Chokay («Turkestan autonomy») and Abdurauf Fitrat («Chagatay Gurungi»). Fearing the unification of the Turkic peoples, the Soviet authorities decided to study the common literary language of the Turkic Muslim peoples within the framework of one nation